Training teachers in the Use of ICT and Teaching Greek as a Second Language in Cyprus: the design, trial and evaluation of a blended teacher training curriculum, part of a European Socrates, Comenius 2.1 project - Papadima-Sophocleous, Salomi (My University, 2008)
The European Curricula in New Technologies and Language Teaching (ECNTLT) programme (Socrates, Comenius 2.1 Action, 2003-2006) dealt with the development of teacher-training curricula for the use of Information and Communications Technologies (ICT) in language teaching. Participating teams came from teacher training European institutions from twelve European countries. The main aim was to enable language teachers of different European languages, most noticeably of the less widely taught and spoken ones, to acquire the necessary knowledge and skills to effectively implement new technologies in their own classroom. The objectives were to produce European curricula leading to internationally recognised certificates in new technologies and language teaching. Within this European programme and based on the needs analysis carried out, the participating Cypriot team developed a curriculum which aimed to help teachers of Greek as an L2 in Cyprus acquire the necessary knowledge and skills to teach Greek as an L2 and at the same time implement new technologies in their own classroom. This paper presents the theoretical framework, and a description of the development, the pilot study and the initial evaluation of this curriculum.
Keywords: Second language; Teacher training; New technologies